Effect of Financial Information and Corporate Social Responsibility Disclosure on Investment Decision: Evidence from an Experimental Study - Rokhayati, Hijroh; Nahartyo, Ertambang; H, Haryono (Asian Journal of Business and Accounting, 2019)
Manuscript type: Research paper Research aims: This research is based on an experiment which is conducted to examine the effects of financial information and corporate social responsibility (CSR) disclosure on investment decision. Design/Methodology/Approach: The research employs the laboratory experiment design which involves 45 graduate students as subjects. The independent variable, financial information, is manipulated by favourable and unfavourable financial information while the CSR disclosure is manipulated by prevention focus and promotion focus. The dependent variable, investment decision, is manipulated by using the 10-point Likert scale. Subjects are randomly assigned to one of four treatments (favourable or unfavourable financial information and promotion focus or prevention focus of CSR disclosure). Research findings: The results show that CSR disclosure affects investment decision. The results also show that subjects decide on greater investments when the CSR disclosure is with a prevention focus. Theoretical contribution/Originality: By investigating the effect of financial information and CSR disclosure on investment decision, this research has effectively used the CSR disclosure strategy to determine investment decision. This research contributes to extant literature by highlighting that CSR disclosure based on regulatory focus can be more effective for investment decision, especially when it has a prevention focus. This persuades investors to make their investment decision. Practitioner/Policy implication: The findings of the current research show that investors make greater investments in financial information and CSR disclosure with a prevention focus. The findings of this research will encourage firms to disclose their CSR activities by taking into consideration the situational aspects, based on the prevention focus that emphasises on avoiding social and environmental negative effects. Research limitation/Implications: This research only examines the situational focus of regulation on investment decision. Future research can examine the effect of chronic regulatory focus on investors. Keywords: Financial Information, Corporate Social Responsibility, Regulatory Focus Theory, Experimental Design, Investment Decision JEL Classification: M41